Participation of vitamin D-upregulated protein 1 (TXNIP)-ASK1-JNK1 signalosome in the enhancement of AML cell death by a post-cytotoxic differentiation regimen. Issue 187 (March 2019) - Wang, X.; Nachliely, M.; Harrison, J.S.; Danilenko, M.; Studzinski, G.P.
Graphical abstract: Highlights: A vitamin D2 analog (D2) combined with a plant-derived antioxidant carnosic acid (CA) can potentiate the therapeutic effect of AraC on AML blasts. D2/CA activates apoptotic signals in cells with DNA damage resulting from AraC treatment. Vitamin D-upregulated protein TXNIP is a regulator of the apoptotic cascade triggered by the differentiation agents (D2/CA) in this system. TXNIP targets the apoptosis signal regulating kinase ASK1, which then sequentially activates MKK4 and JNK and the executioners of apoptosis. These data may provide a paradigm for future improvements of Cytarabine-based therapy of patients with AML. Abstract: Standard therapy for Acute Myeloid Leukemia (AML) is rarely curative, and several suggested improvements have had little success so far. We have reported that in an in vitro model of a potential therapeutic regimen for AML, the activity of cytarabine (AraC) is enhanced by a sequential treatment with a combination of the vitamin D2 analog Doxercalciferol (D2) and the plant-derived antioxidant carnosic acid (CA). Importantly, the enhancement occurred selectively in patient-derived AML blasts, but not in the normal bone marrow cells. We now demonstrate that TXNIP, previously known as Vitamin D up-regulated protein 1 (VDUP1) [PMID 808674] plays a part in signaling cell death (CD) in this regimen. This is shown by the reduced CD when TXNIP protein levels are decreased by the CRISPR/CAS9 or RNAi technology. Further, we show that direct activation of ASK1 kinase by TXNIP is required for the optimal transmission of the CD signal to apoptotic machinery, regulated by JNK and BIM. These studies provide a rationale for a projected clinical trial of this vitaminD -based new therapeutic regimen for AML.